VARIASI MORFOLOGI ANDALIMAN (ZANTHOXYLUM ACANTHOPODIUM) DI SUMATRA UTARA - Romaita Newanti Lumban Raja; Alex Hartana (Floribunda, 2017)
Romaita Newanti Lumban Raja & Alex Hartana. 2017. Morphologycal Variation of Andaliman (Zanthoxylum acanthopodium) in North Sumatra. Floribunda 5(7): 258–266. — Andaliman plants (Zantoxylum acanthopodium DC.) found in North Sumatra, Indonesia, and known as seasoning plants  or 'merica Batak’  in Batak dishes. This study was conducted to explore the diversity of andaliman plants in North Sumatra.  27  andaliman plants collected and  analyzed  based on  their 24 morphological characters of stems, leaves, flowers, fruits, and seeds  using  unweighted pair group method with arithmatic average (UPGMA) and clustered  based on similarity for qualitative data (SIMQUAL) and coefficient simple matching, using NTSYS pc. 2.02 version. The phenetic analysis showed dendrograme of 27 andaliman plants in North Sumatra were clustered into 4 groups. The main characters differentiate each group are the color of young branches, thorns on leaf  midrib, the color of calyx, and the color of  fruit. The group I  and II in dendrograme refer  to local cultivar names ‘Simanuk’ and ‘Sihorbo’, while the group III and IV refer to ‘Silokot’ and ‘Sikoreng’ cultivars. An identification key for  the four andaliman cultivars is presented. Keywords: Andaliman, Character, Clustering, North Sumatra, Morphology, Zantoxylum acanthopodium.  Romaita Newanti Lumban Raja & Alex Hartana. 2017. Variasi Morfologi Andaliman (Zanthoxylum acanthopodium) di Sumatra  Utara. Floribunda 5(7): 258–266. — Andaliman (Zantoxylum acanthopodium DC.) di Indonesia banyak terdapat di Sumatra Utara dan digunakan sebagai bumbu masakan khas suku Batak. Eksplorasi keberagaman andaliman telah dilakukan dan diperoleh 27 nomer sampel. Analis fenetik berdasarkan 26 karakter morfologi terhadap 27 sampel telah dilakukan dengan metode UPGMA melalui program NTSys versi 2.02. Dendrogram yang dihasilkan menunjukan ada 4 kelompok andaliman yang terpisah berdasarkan karakter utama yang membedakan setiap kelompok yaitu warna dahan muda, rambut pada dahan, onak pada ibu tulang daun, warna kelopak bunga, dan warna buah. Berdasarkan klasifikasi masyarakat, kelompok I dan II  merujuk pada kultivar ‘Simanuk’ dan ‘Sihorbo’. Sedangkan kelompok III dan IV merujuk pada kultivar ‘Silokot’ dan ‘Sikoreng’. Hasil pengelompokan kemudian digunakan untuk pembuatan kunci identifikasi.Kata kunci: Andaliman, karakter, pengelompokan, Sumatra Utara, morfologi, Zantoxylum acanthopodium.